STRATEGI PEMASARAN TERHADAP K-STREET BYUNDONG DALAM MENGHADAPI PASAR DI ERA PANDEMI COVID-19 DI KOTA PURBALINGGA - Yeristha Asrillia, Auriel; Rohmah, Fitri Nur; Mawarni, Mita; Prasetyani, Oki Dwi (UNPERBA, 2022)
MSMEs are trading businesses managed by individuals who have economic businesses with criteria that have been applied by law. Even in terms of management, it still has a close relationship with the community's economy. However, around the beginning of March 2020, Indonesia was hit by an outbreak of a disease called Covid-19 (Corona Virus). Corona virus is a contagious disease. The global Covid-19 pandemic certainly has an impact on various sectors, especially in the economic sector. This study aims to examine the strategy of K-Street ByungDong in dealing with the market in the era of the Covid-19 pandemic and find out the efforts made by K-Street ByungDong in overcoming marketing constraints during the Covid-19 pandemic. The research method used in this study is a descriptive qualitative method. In this study, the object of research is the strategy of K-Street ByungDong in dealing with the market in the era of the Covid-19 pandemic. Data analysis methods used are interviews and documentation. Based on the results of the study, it shows that digital marketing is effectively carried out as a marketing strategy in dealing with the market in the era of the covid-19 pandemic